(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Even though the states have constitutionally guaranteed powers, the constitution provides mechanism by which these powers can be exercised by the centre especially through the Governor. Governor serves as the cord between the centre and the states. The Constitution grants the Centre of full powers as regards to the appointment of the Governor. The role of the Governor is twofold- firstly as Head of the state and secondly as the representative of the Centre. He works as the channel of communication between the Centre and the states. Governor holds a wide degree of discretionary powers over the functioning of the state machinery. He can have a lot of impact upon the working of the state legislature during ‘fair weather’ as well as during the Emergency. As the Governor is appointed by the President, which indirectly leads to his appointment being made by the Council of Minister[1], the Central Government can creep into the works of the state government by this route. So the role and influence of the Governor must be critically examined.